2021
DOI: 10.31234/osf.io/4x8zu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrospective and prospective prioritization in visual working memory

Abstract: A growing body of research indicates that items assigned with a higher ‘value’ prior to presentationare better recalled in working memory tasks. This has been interpreted as reflecting the strategic prioritization of these items via selective attention during encoding, maintenance, and retrieval. The current study sought to establish whether value-based prioritization effects can be obtained in a sequential visual working memory task when value information is provided retrospectively during maintenance and ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…There is, however, some evidence of a primacy advantage using the currently employed cued recall task following explicit instruction to prioritise memory for the first conjunction in the list (Atkinson, Berry, et al, 2018;Hitch et al, 2018;Hu et al, 2014Hu et al, , 2016 although see null effect at serial position 1 reported by Allen et al, 2020). Indeed, participants can prioritise more valuable information in working memory resulting in improved recall for high value items across all serial positions (Allen et al, 2020;Allen & Atkinson, 2021;Atkinson et al, 2020; with prioritisation effects observed also in children and older adult samples, Allen et al, 2020;Atkinson et al, 2019). This memory facilitation for high value items is typically offset by memory decrements to the lower value items in the list.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, some evidence of a primacy advantage using the currently employed cued recall task following explicit instruction to prioritise memory for the first conjunction in the list (Atkinson, Berry, et al, 2018;Hitch et al, 2018;Hu et al, 2014Hu et al, , 2016 although see null effect at serial position 1 reported by Allen et al, 2020). Indeed, participants can prioritise more valuable information in working memory resulting in improved recall for high value items across all serial positions (Allen et al, 2020;Allen & Atkinson, 2021;Atkinson et al, 2020; with prioritisation effects observed also in children and older adult samples, Allen et al, 2020;Atkinson et al, 2019). This memory facilitation for high value items is typically offset by memory decrements to the lower value items in the list.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using reward-based prioritization have traditionally introduced the reward manipulation before encoding. One way to do so is by presenting a reward pattern at the beginning of the trial (e.g., Allen & Atkinson, 2021;Allen & Ueno, 2018;Atkinson et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Using these types of reward-based manipulations of priority in working memory, memory performance has been shown to be better for high-reward items, compared to low-reward items (e.g., Allen & Atkinson, 2021;Allen & Ueno, 2018;Atkinson et al, 2022, associating reward values to item locations; Atkinson et al, 2018;Hitch et al, 2018;Hu et al, 2014Hu et al, , 2016 associating reward values to serial positions). When perceptual interference is shown between encoding and test, high-reward items have been found to suffer more from memory loss due to the presence of perceptual interference than low-reward items, showing prioritized information to be particularly vulnerable to perceptual interference (e.g., Allen & Ueno, 2018, associating reward values to item locations; Hitch et al, 2018;Hu et al, 2014Hu et al, , 2016, associating reward values to serial positions).…”
Section: Methodsmentioning
confidence: 99%
“…But even representations already in VWM can be flexibly updated according to changes in task relevance during maintenance. While information that is no longer important can be removed from memory (e.g., Souza et al, 2014;Williams et al, 2013), maintenance in different representational states established by the allocation of attention can reflect more graded differences in relevance (e.g., Gunseli et al, 2015;LaRocque et al, 2014;Stokes et al, 2020;van Moorselaar et al, 2015)-as established, for instance, by the likelihoods of items to be tested, by the requirements of an upcoming action, or by item value (e.g., Allen & Atkinson, 2021;Heuer et al, 2020;Heuer & Schubö, 2018;. Research on selective processing during maintenance has been fuelled by the introduction of the retrocue paradigm (Griffin & Nobre, 2003;Landman et al, 2003), in which cues presented during the retention interval of a VWM task indicate one or several item(s) as more likely to be subsequently tested (reviewed in Souza & Oberauer, 2016).…”
Section: Introductionmentioning
confidence: 99%